Computer Networks / A Systems Approach - Davie, Bruce S.; Peterson, Larry L. (Elsevier, 2012)
This book teaches you the key principles of computer networks with examples drawn from the real world of network and protocol design. Foreword, Preface, Foundation, Getting Connected, Internetworking, Advanced Internetworking, End-to-End Protocols, Congestion Control and Resource Allocation, End-to-End Data, Network Security, Applications, Glossary, Bibliography, Index.